Regional Variations of Indonesian Cities: Geometric properties, Street Patterns, and Topological structure. - Muhammad Fajri Romdhoni; Mahbub Rashid (Journal of Regional and City Planning, 2022)
Abstract: As one of the fastest growing countries with the largest population in the ASEAN region, cities in Indonesia are constantly evolving and changing. Although the current political establishment is planning to relocate the country’s capital to the Kalimantan island, comparative research on Indonesian cities is very limited. Indonesia is an archipelago country that consists of 17,508 islands and at least 514 urban areas, of which 98 of them can be categorized as cities. This paper will focus on examining variations in provincial capital cities from Indonesia’s 6 regions: Sumatera, Java-Bali, Nusa Tenggara, Kalimantan, Sulawesi, Maluku-Papua. The paper uses OpenStreetMap (OSM) vector datasets to study the geometric properties of street centerlines and the regression techniques on the Landsat satellite images of these cities processed in GIS to study land-use patterns. The paper also uses the method of patterns classification from volunteered geographic information systems (VGI) to study street orientational patterns utilizing OSMnx. Finally, the paper uses space syntax methods to describe the topological features of natural street networks of the cities. The results of this study show that there are statistically significant regional variations among cities in Indonesia. They also show that street network orientations are correlated with global integration values indicating that movement potentials could be affected by spatial shape patterns in these cities.